2023
DOI: 10.1002/cam4.6166
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of distant metastasis and specific survival prediction of small intestine cancer patients with metastasis: A population‐based study

Abstract: BackgroundSmall intestine cancer (SIC) is difficult to diagnose early and presents a poor prognosis due to distant metastasis. This study aimed to develop nomograms for diagnosing and assessing the prognosis of SIC with distant metastasis.MethodsPatients diagnosed with SIC between 2010 and 2015 were included from the Surveillance, Epidemiology and End Results database. Univariate and multifactor analysis determined independent risk factors for distant metastasis and prognostic factors for overall and cancer‐sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…These compelling results provide clinicians with evidence to effectively persuade hesitant patients about the substantial benefits of surgery and chemotherapy. It is widely believed that older age in duodenal cancer patients with DM is associated with a poorer OS prognosis than in younger patients[ 14 ]. Our study affirmed that older patients indeed had a higher likelihood of experiencing a poorer OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compelling results provide clinicians with evidence to effectively persuade hesitant patients about the substantial benefits of surgery and chemotherapy. It is widely believed that older age in duodenal cancer patients with DM is associated with a poorer OS prognosis than in younger patients[ 14 ]. Our study affirmed that older patients indeed had a higher likelihood of experiencing a poorer OS.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a scarcity of studies offering dependable data regarding the association between clinicopathological characteristics and metastatic patterns in duodenal cancer. Furthermore, there is a lack of established predictive models for determining the likelihood of DM in duodenal cancer or for predicting the prognosis of patients with duodenal cancer and DM[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These ndings provide compelling evidence for clinicians to effectively persuade hesitant patients about the substantial bene ts of surgery and chemotherapy. It is generally believed that duodenal cancer patients with DM of older age have a poorer OS prognosis than younger patients [14] . Our study showed that older patients were more likely to have a poorer OS.…”
Section: Discussionmentioning
confidence: 99%
“…DPCs in the early stage are mistaken for chronic inflammation or benign protuberant lesions due to their small size, as determined by CT, endoscopic examination and other methods. Furthermore, the incidence of small intestinal carcinoma and DPC has increased annually, and the mortality rate has increased by 26% [ 3 ]. As many patients are asymptomatic until advanced disease detection through imaging examination, diagnostic delays often occur, leading to a poor prognosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As many patients are asymptomatic until advanced disease detection through imaging examination, diagnostic delays often occur, leading to a poor prognosis [ 4 ]. Previous studies have shown that more than 56% of patients exhibit locally advanced tumours or distant metastases at initial diagnosis, and those with advanced tumours only have a 5-year survival rate of 42.6% [ 3 ]. For papilla tumours in situ without lymphovascular invasion (LVI) or lymph node metastasis (LNM), endoscopic papillectomy is safe and curative; however, when tumours exhibit LNM or LVI, surgery is considered the first modality without considering endoscopy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%